Enacting Wonder-infused Pedagogy in an Elementary Science Methods Course - Gilbert, Andrew; Byers, Christie C. (Innovations in Science Teacher Education, 2019)
Future elementary teachers commonly experience a sense of disconnection and lack of confidence in teaching science, often related to their own negative experiences with school science. As a result, teacher educators are faced with the challenge of engaging future teachers in ways that build confidence and help them develop positive associations with science. In this article, we present wonder-infused pedagogy as a means to create positive pathways for future teachers to engage with both science content and teaching. We first articulate the theoretical foundations underpinning conceptions of wonder in relation to science education, and then move on to share specific practical activities designed to integrate elements of wonder into an elementary methods course. We envision wonder-infused pedagogy not as a disruptive force in standard science methods courses, but rather an effort to deepen inquiry and connect it to the emotive and imaginative selves of our students. The article closes with thorough descriptions of wonder related activities including wonder journaling and a wonder fair in order to illustrate the pedagogical possibilities of this approach. We provide student examples of these artifacts and exit tickets articulating student experiences within the course. We also consider possible challenges that teacher educators may encounter during this process and methods to address those possible hurdles. We found that the process involved in wonder-infused pedagogy provided possibilities for future teachers to reconnect and rekindle a joyful relationship with authentic science practice.